Competing A‐site and B‐site doping effects on magneto‐transport of RE0.55 Sr0.45 Mn1−x Rux O3 manganites in the vicinity of the SGI and FMM border. Issue 10 (25th July 2013) - Alagoz, H. S.; Živković, I.; Mahmud, S. T.; Saber, M. M.; Perrin, G.; Shandro, J.; Khan, M.; Zhang, Y.; Egilmez, M.; Jung, J.; Chow, K. H.
<x xml:space="preserve">Abstract</x> Competing effects of the A—site and B—site doping on the magneto—transport have been investigated in RE0.55Sr0.45Mn1−xRuxO3 (0 ≤ x ≤ 0.25) manganites with RE (A—site) = GdySm1−y (0 ≤ y ≤ 1). The Ru (B—site)‐free system is a ferromagnetic metal (FMM) for y ≤ 0.5 and a spin—glass insulator (SGI) for y > 0.5. For y ≤ 0.5, Ru improves the metallicity compared to the Ru—undoped system. For y > 0.5, Ru—doping induces a transition from the SGI to FMM state, above a percolation threshold which depends strongly on the A—site substitution. Interestingly, irrespective of the A—site doping level y, the percolation is suppressed when the Ru concentration x exceeds ∼16% to 18%.